Regional Geological Survey of Hanggai, Xianxia and Chuancun, Zhejiang Province in China 1:50,000 Geological Maps - Zhang, Jianfang (The China Geological Survey Series, 2020)
This Open Access book introduces readers to the regional geology of Hanggai, Xianxia and Chuancun, the area between China's northern Zhejiang Province and southern Anhui Province and explores the strata, magmatic rocks and tectonic structures in 1:50,000 scale geological maps. Based on studies of multiple stratigraphic divisions, the standard stratigraphic section of the upper Ordovician Hirnantian in the lower Yangtze region is established, revealing for the first time numerous "Burgess Shale-type" sponge fossils in Hirnantian strata and identifying 10 grapholite fossil belts and various fossil categories, including chitin, trilobites, gastropods, brachiopods, and cephalopods. Moreover, the book identifies for the first time Late Ordovician volcanic events in northern Zhejiang province. The work represents a major contribution to research on Paleozoic strata in the Lower Yangtze region, and sheds new light on understanding the Hirnantian glacial event and biological extinction event in South China by providing a high-precision time scale. In addition, the book opens an important avenue for future research on sponge evolution after the Cambrian life explosion. As such, it offers a unique and valuable asset for researchers and graduate students alike.